2011
DOI: 10.1007/s10549-011-1753-2
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Src in breast cancer cell migration and invasion in a breast cell/bone-derived cell microenvironment

Abstract: The preferential metastasis of breast cancer cells to bone comprises a complex set of events including homing and preferential growth, which may require unique factors produced by bone or other cells in the immediate microenvironment. In this study, an in vitro co-culture system composed of bone mesenchymal stem cells and breast cancer cell lines is used to examine the role of Src kinase on breast cancer cell migration and invasion in the presence of bone-derived cells. This research shows that Src kinase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…Src proteins appear to be important for multiple aspects of tumor progression, including proliferation, disruption of cell-cell contacts, migration and invasiveness [61]. TAM and CXB additively reduced tumor migration and invasion; this finding was supported by our wound-healing and Boyden chamber assay results.…”
Section: Discussionsupporting
confidence: 74%
“…Src proteins appear to be important for multiple aspects of tumor progression, including proliferation, disruption of cell-cell contacts, migration and invasiveness [61]. TAM and CXB additively reduced tumor migration and invasion; this finding was supported by our wound-healing and Boyden chamber assay results.…”
Section: Discussionsupporting
confidence: 74%
“…2 Elevated Src activity in cancer is also linked to increased cellular invasion and progression-related events like EMT, 34 influences actin dynamics and invasion 35 and has been implicated in cancer cell migration and invasion to a bone derived microenvironment. 36 Src activity is also associated with cell cycle arrest, 37 has implications on cellular functions in triple negative breast cancer 38 and has significance in prostate cancer progression. 39 Finally, expression of Src is associated with FAK activity and specifically monitors focal adhesion dynamics to control cellular functions like migration and focal adhesion turnover.…”
Section: Discussionmentioning
confidence: 99%
“…We found that GRPr signaling upregulated the expression of SRC , MYOF , and TWIST in prostate cancer cells. Previous studies have shown that these genes are important for inducing migration of various cancer cells [63–65]. …”
Section: Discussionmentioning
confidence: 99%
“…We found that GRPr signaling upregulated the expression of SRC, MYOF, and TWIST in prostate cancer cells. Previous studies have shown that these genes are important for inducing migration of various cancer cells [63][64][65]. Although the role of the GRPr signaling pathway is not completely understood in bone metastasis, it has been shown that bombesin antagonists decreased bone metastasic growth and invasiveness of PC3 prostate cancer cells in nude mice [66].…”
Section: Discussionmentioning
confidence: 99%